Innovations for Enhancing Efficiency in Warehousing and Distribution Center Operations - Rasamee, Samitra; Chienwattanasook, Krisada (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This article aims to analyze the impact of innovation and automation technology on increasing the efficiency of warehouse and distribution centers, considering both positive and negative aspects. By focuses on the most important aspects, including the impact on the workforce, workforce development for automation, high investment costs, and data security when implementing technology into operational processes. This article utilizes literature review methodology, compares different approaches to technology adoption in warehouse operations, and presents management strategies to overcome the challenges posed by these technological shifts. The article explains that automation systems significantly improve operational efficiency, reduce long-term costs and increase logistical flexibility. However, the introduction of automation reduces repetitive tasks while increasing the demand for technology management and data analysis positions. Companies must therefore introduce training programs for their employees and lifelong learning strategies to facilitate workforce adaptation. In terms of investment, automation requires high initial costs, but a systematic and gradual investment approach can mitigate financial risks. In terms of data security, companies should prioritize cybersecurity measures to protect digital operations. Looking to the future, warehouses and distribution centers will evolve into intelligent systems capable of optimizing processes proactively and autonomously. In addition, sustainable operating practices will gain in importance and further strengthen the competitiveness of companies in the long term. Article history : Received 12 March 2025 Revised 30 April 2025 Accepted 2 May 2025 SIMILARITY INDEX = 4.49 %